Assessing factors Affecting Academic Performance of Orphaned Children in Primary Schools in Zimbabwe - Majoni, Angeline; Majoni, Cuthbert (IJRDO- Journal of Educational Research, 2016)
The study sought to find out the factors affecting academic performance of orphaned children in Bindura District primary schools in Zimbabwe. The descriptive survey design was used in this study. The population was 300 teachers and 50 orphaned children. A sample of 80 teachers and 10 children randomly selected participated in this research study. Data were collected using questionnaires and interviews. The SPSS programme was used to analyse the data. The study found out that orphaned children did not perform well academically during class work. They did not do homework assigned by the teachers. The study found out that teachers did not have knowledge or skills to assist orphaned children during teaching and learning. The study recommended that teachers should be equipped with skills to manage orphaned children academically. The study recommended that foster parents need to be made aware through workshops how to assist orphaned children with class work assigned to be done at home. More research should be done on how orphaned children can be motivated to learn